1983
DOI: 10.2337/diab.32.5.433
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of GIP in Spontaneous Syndromes of Obesity and Diabetes in Mice

Abstract: The role of GIP in the pathogenesis of spontaneous syndromes of obesity-diabetes was examined in ob/ob mice of the Aston stock and db/db mice of the C57BL/KsJ background. Compared with lean controls, fed adult ob/ob and db/db mice, respectively, exhibited 1.8-fold and 2.1-fold increases in body weight, 1.8-fold and 2.8-fold elevations of plasma glucose, and 15.4-fold and 5.6-fold elevations of plasma insulin. As indicated by the relative magnitude of the hyperglycemia and hyperinsulinemia, db/db mice displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 0 publications
4
47
0
Order By: Relevance
“…The particularly potent stimulation of GIP secretion after high-fat feeding [27] suggests a role for GIP in fat metabolism [20]. Consistent with this, plasma GIP concentrations have been reported to be elevated in obesity-related type 2 diabetes [28] and animals with obesity-related diabetes [29]. Experimental evidence in mice also indicates that inhibition of GIP signalling by genetic knockout of the GIP receptor prevents diet-induced obesity through the preferential use of fat as an energy substrate [30].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The particularly potent stimulation of GIP secretion after high-fat feeding [27] suggests a role for GIP in fat metabolism [20]. Consistent with this, plasma GIP concentrations have been reported to be elevated in obesity-related type 2 diabetes [28] and animals with obesity-related diabetes [29]. Experimental evidence in mice also indicates that inhibition of GIP signalling by genetic knockout of the GIP receptor prevents diet-induced obesity through the preferential use of fat as an energy substrate [30].…”
Section: Introductionmentioning
confidence: 77%
“…More recently it has been shown that obese diabetic (ob/ob) mice have intestinal K cell hyperplasia, markedly elevated concentrations of intestinal (2.8-fold increase) and circulating GIP (15.1-fold increase) [29,40,41] and display a diminished insulinotropic response to native GIP [11]. Additionally, ob/ob mice genetically manipulated to knock out GIP receptor function displayed significant amelioration of adiposity [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, the bridge between high-fat obesitogenic diet and obesity comorbidities is not fully understood. High-fat feeding, such as that used in the present study, allows intestinal K-cell hyperplasia, enhancing GIP gene expression together with intestinal GIP content, ultimately resulting in high basal and feedinginduced circulating levels of GIP [6][7][8][9]. The role played by GIP in mediating the effects of HFD, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…High-fat feeding induces K cell hyperplasia and glucosedependent insulinotropic polypeptide (GIP) secretion [6][7][8][9] with insulin secretion potentiating effects [10]. Blockade of GIP action by administration of a specific GIP receptor antagonist, (Pro 3 )GIP, reverses the glucose intolerance induced by HFD [11] without affecting circulating insulin concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Animal models of obesity-diabetes syndromes support a role for an overactive EIA in the metabolic disturbance. The genetically-obese (ob/ob) mouse exhibits hyperplasia of intestinal GIP-secreting cells and circulating GIP and insulin levels are raised (Flatt et al 1983). Circulating GLP-1(7-36)amide levels cannot be measured in reasonable blood volumes in these animals, but intestinal levels are elevated when compared with homozygous lean littermates and these animals can respond to exogenous GLP-1(7-36)amide administration .…”
Section: Obesity and Non-insulin-dependeni Diabetes Mellitusmentioning
confidence: 99%